Using cortico-muscular and cortico-cardiac coherence to study the role of the brain in the development of muscular fatigue. (February 2019) - Martínez-Aguilar, Gloria Mónica; Gutiérrez, David
Highlights: We propose a method to analyze cortico-muscular and cortico-cardiac coupling during a cycling exercise in order to study the development of muscular fatigue. The proposed experimental protocol allows any person to be assessed based on their own individualized fatigue thresholds, then our proposal can be used not only for training, but also for clinical purposes. We use the coherence as a metric to understand the coupling between electroencephalography, electromyography, and electrocardiography signals, then we relate such coupling to the influence that performance fatigability and the perception of fatigue may have between each other. Abstract: We propose a method to analyze cortico-muscular and cortico-cardiac coupling during a cycling exercise in order to study the development of muscular fatigue. Our analysis is based in finding statistically significant changes in the coherence between electromyography (EMG) and electrocardiography (ECG) when compared against electroencephalography (EEG) signals. The coherence is a measure of the degree of correlation of the spectral power in an specified bandwidth between two signals, then EMG-EEG and ECG-EEG coherences are here analyzed during the development of muscular fatigue. For that purpose, we propose an experimental protocol in which a personalized fatigue threshold is found for the volunteers, then different levels of physical exertion are considered. Our results showed significant changes in the maximum cortico-muscular coherence in the β brain rhythm as the exercise progresses and fatigue develops, as well as changes in the maximum cortico-cardiac coherence, again in the β band, from the beginning to the end of the exercise protocol.